1988
DOI: 10.1159/000281306
|View full text |Cite
|
Sign up to set email alerts
|

Paratesticular Papillary Mesothelioma

Abstract: A case of uncommon paratesticular mesothelioma in a young patient is presented. Its questionable malignancy, as well as the method of treatment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other possible etiological factors that have been suggested for malignant disease include previous testicular trauma and hernia repair; however these factors have not been corroborated (Amin, 1995;Antman et al, 1984). In the few cases reported in patients in the first three decades of life, no history of asbestos exposure was reported in the patient or family and the etiological factor in these cases remains unclear (Antman et al, 1984;Johnson et al, 1973;Jones et al, 1995;Linn et al, 1988;McDonald et al, 1983;Plas et al, 1998;Stein and Henkes, 1986).…”
Section: Tunica Vaginalis Testismentioning
confidence: 99%
“…Other possible etiological factors that have been suggested for malignant disease include previous testicular trauma and hernia repair; however these factors have not been corroborated (Amin, 1995;Antman et al, 1984). In the few cases reported in patients in the first three decades of life, no history of asbestos exposure was reported in the patient or family and the etiological factor in these cases remains unclear (Antman et al, 1984;Johnson et al, 1973;Jones et al, 1995;Linn et al, 1988;McDonald et al, 1983;Plas et al, 1998;Stein and Henkes, 1986).…”
Section: Tunica Vaginalis Testismentioning
confidence: 99%
“…More commonly found in the peritoneal cavity, these neoplasms, referred to as well-differentiated papillary mesothelial tumor (WDPMT) or well-differentiated papillary mesothelioma (WDPM), are rarely seen in the testis. Initially described in 1957 by Bárbera et al, a few dozen such tumors have to date been reported in the literature, one of the most important series reported being the work of Brimo et al [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Typically, these neoplasms show no architectural complexity, whereas borderline tumors with more complex architectures or areas of uncertain invasion are reported and pose a diagnostic challenge as there is an ongoing debate about whether to classify these as benign or of uncertain malignant potential, with consequences for further patient management and patient perception of their illness. 4,5,8,15 In recent years, new molecular analytical tools, including BAP1 immunohistochemistry, have emerged, probably aiding in the diagnostic classification.…”
Section: Introductionmentioning
confidence: 99%